Avaliação do nível de prontidão de tecnologias desenvolvidas em Instituições de Ciência e Tecnologia - Bergamini, Ricardo Luiz (2019)
This research aims to create a tool which defines, through questionnaires, at what level of technological maturity is the product under development, called “TRL Calculator”. To this end, a survey was initially carried out on the models of assessment of technological maturity levels currently available in the Science and Technology Institutions (ICTs); Subsequently, we discuss the importance of the presence of tools that can analyze whether a product under development is ready to be released to the market without any harm to any of the parties involved. In this direction, this qualitative research sought to develop an electronic spreadsheet to calculate the readiness of these products, which was evaluated by four public educational institutions, three from Roraima (Roraima Federal University, Roraima State University and Roraima Federal Institute). and one from Santa Catarina (Catarinense Federal Institute), and one from research, EMBRAPA Roraima. The spreadsheet was tested and its potential evaluated by the Technological Innovation Centers (NITs) of these institutions, in order to adapt it to their respective demands by evaluating the maturity levels. After exhaustive evaluation by the institutions, they reached the verdict of the viability and applicability of the tool with the respective NITs. Based on the results, and based on the nine levels of technology maturity assessment, Technology Readiness Levels (TRL), used to evaluate the technological readiness of the products surveyed, it was possible to improve the processes of evaluation of the products maturity level. and technologies in development in Higher Education Institutions and Science and Technology Institutions, consequently, assisting them in the task of modernizing their respective practices related to innovation.